Numerical analysis of entropy generation due to natural convection in three-dimensional partially open enclosures - Öztop, Hakan Fehmi; Kolsi, Lioua; Alghamdi, Abdulaziz; Abu-Hamdeh, Nidal; Borjini, Mohamed Naceur; Ben Aissia, Habib (Elsevier Science Bv, 2017)
Three-dimensional computational analysis of entropy generation due to natural convection in partially open enclosure has been performed in this work by using finite volume method. A written computer code was developed to solve governing equations of this three-dimensional problem. The study has been performed for different governing parameters such as opening ratio 0. 25 <= h <= 0.75, center of opening 0.25 <= d <= 0.75 and Rayleigh number 10(3) <= Ra <= 10(5). It is observed that edge of openings is the most effective parameter on entropy generation and after comparing many cases, both the highest heat transfer and entropy generation were observed for the fully opened cavity. (C) 2017 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Natural convection; Entropy generation; Three dimensional; Open enclosure